2016
DOI: 10.1037/a0039923
|View full text |Cite
|
Sign up to set email alerts
|

When asking the question changes the ultimate answer: Metamemory judgments change memory.

Abstract: Self-report measurements are ubiquitous in psychology, but they carry the potential of altering processes they are meant to measure. We assessed whether a common metamemory measure, judgments of learning, can change the ongoing process of memorizing and subsequent memory performance. Judgments of learning are a form of metamemory monitoring described as conscious reflection on one's own memory performance or encoding activities for the purpose of exerting strategic control over one's study and retrieval activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
157
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(184 citation statements)
references
References 92 publications
17
157
3
Order By: Relevance
“…Many studies have shown reactive effects of immediate JOLs (JOLs that take place immediately following learning) on memory performance (Mitchum, Kelley, & Fox, 2016;Soderstrom, Clark, Halamish, & Bjork, 2015). In some of these studies, the act of making an immediate JOL during learning is found to improve later memory performance (Soderstrom, et al 2015), whereas other studies show that making JOLs leads to poorer memory performance relative to a no-judgment control (Mitchum et al, 2016). Retrieval attempts are not expected to take place prior to immediate JOLs as there is no delay between learning and judgment, suggesting that benefits, when they occur, are likely due to the judgment itself, perhaps by enticing participants to engage in a form of elaboration during learning.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown reactive effects of immediate JOLs (JOLs that take place immediately following learning) on memory performance (Mitchum, Kelley, & Fox, 2016;Soderstrom, Clark, Halamish, & Bjork, 2015). In some of these studies, the act of making an immediate JOL during learning is found to improve later memory performance (Soderstrom, et al 2015), whereas other studies show that making JOLs leads to poorer memory performance relative to a no-judgment control (Mitchum et al, 2016). Retrieval attempts are not expected to take place prior to immediate JOLs as there is no delay between learning and judgment, suggesting that benefits, when they occur, are likely due to the judgment itself, perhaps by enticing participants to engage in a form of elaboration during learning.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason is that previous studies showed that asking participants to make JOLs affects their self-regulated study time allocation. For example, when expecting to make JOLs people may spend some time considering the memorability of an item, and devote a portion of the encoding time to assessing their on-going learning status (Mitchum, Kelley, & Fox, 2016). Therefore, to directly explore the forward testing effect on metamemory monitoring, we employed an experimenter-paced procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Self-reports rely on introspection, which risks being incomplete, biased, or based heavily on inference due to failures of memory when collected after the fact (Ericsson & Simon, 1993). If strategies are assessed during encoding, the reports themselves are more accurate, but the solicitation may lead subjects to change strategies (cf., Mitchum, Kelley, & Fox, 2016).…”
Section: Strategy Use and Working Memory Capacitymentioning
confidence: 99%